2015
DOI: 10.1111/jop.12391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prolidase activity and oxidative stress in patients with oral lichen planus and oral lichenoid contact reactions

Abstract: The findings of this study suggest an increased prolidase activity and oxidative stress and imbalance in the antioxidant defense system in biological fluids of patients with OLP and OLCR when compared with the healthy subjects. Both OLP and OLCR patients revealed almost similar prolidase activity and oxidative stress levels although these two conditions have different etiopathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…These data highlight the potential of NAC for clinical application as an osteogenic enhancer in bone regeneration therapies. Significantly higher salivary ROS, lipid peroxidation, and NO and nitrite levels are present in oral lichen planus patients [ 34 ], suggesting antioxidants such as NAC have therapeutic potential in managing this disease.…”
Section: Antioxidation Activitymentioning
confidence: 99%
“…These data highlight the potential of NAC for clinical application as an osteogenic enhancer in bone regeneration therapies. Significantly higher salivary ROS, lipid peroxidation, and NO and nitrite levels are present in oral lichen planus patients [ 34 ], suggesting antioxidants such as NAC have therapeutic potential in managing this disease.…”
Section: Antioxidation Activitymentioning
confidence: 99%
“…In general, several predisposing factors including immunity, infection, genetics, stress and endocrine have been implicated in OLP generating and progressing. Recent studies reported an increased prolidase activity and oxidative stress in patients with OLP, implicating an imbalance in the antioxidant defense system (Ergun et al, 2011;Batu et al, 2016). Although the precise etiology is still unclear, evidence points out that OLP is an immunological process which is triggered by an unknown antigen that alters the basal keratinocytes of the oral mucosa and these changes make the keratinocytes susceptible to cell immune response (Ismail et al, 2007;Payeras et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The role of oxidative stress in the molecular etiology of OLP has been highlighted by recent studies (38,39). As evidence of oxidative stress, patients with OLP have high levels of lipid peroxidation products such as malondialdehyde (MDA) and 4-hydroxy-2-nonenal (40,41). Although their role in OLP is not clear, these oxidative stress markers trigger a sequence of biological responses (including apoptosis initiation) by influencing the levels of B-cell lymphoma 2 and BCL2-associated X proteins, the recruitment of pro-inflammatory T-lymphocytes and nuclear localization and activity of factor kappa B (42,43).…”
Section: Resultsmentioning
confidence: 99%